On mysterious occurrence of butterflies in the genus Delias at Jinmen Islands, with clarification on the nomenclature of D. pasithoe (Linnaeus, 1767) and D. acalis (Godart, 1819) in southern China - Hsu, Yu-Feng; Huang, Hang-Chi; Lu, Chen-Chih (Zootaxa, 2017)
In recent years, a considerable number of pierid butterflies of the genus Delias have been found from Jinmen Islands, where no available hostplants grow, rendering a proof of cross sea water migration of these butterflies. It is suggested here that these butterflies come from nearby continent of eastern China, visiting the islands for nectar acquisition in seasons when nectar is in short supply because they mostly show up in autumn months. Samples obtained during the survey contained two species, namely Delias pasithoe (Linnaeus, 1767) and Delias acalis (Godart, 1819). Subspecific names applied to both species in eastern China appear to involve nomenclatural problems, with erroneous usage in recent literature.